1999
DOI: 10.1097/00042560-199909010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates HIV-1 Replication

Abstract: Although nitric oxide (NO) production is increased in HIV-1-infected patients, and NO is known to inhibit the replication of several viruses, very little is known about the effects of NO on HIV-1 replication. In the present studies, we find that S-nitrosothiols (RSNOs), a class of NO donor compounds present in the human circulatory system, inhibit HIV-1 replication in acutely infected human peripheral blood mononuclear cells (PBMCs) and have an additive inhibitory effect on HIV-1 replication in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 53 publications
0
29
1
Order By: Relevance
“…In addition, it has been reported that the NO donor, S-nitrosoglutathione (GSNO), decreases viral replication in PBMC (39). The reasons for the discrepancies with our results are unknown, but they may depend on the different NO donors used that varied in the speed and amount of NO released.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In addition, it has been reported that the NO donor, S-nitrosoglutathione (GSNO), decreases viral replication in PBMC (39). The reasons for the discrepancies with our results are unknown, but they may depend on the different NO donors used that varied in the speed and amount of NO released.…”
Section: Discussioncontrasting
confidence: 78%
“…At those concentrations, no effect on cell proliferation or cell survival was observed. In contrast, others have shown that high concentrations of NO (as those supplied by GSNO) inhibit NF-B activation (13,51,58) and HIV-1 replication (39). At those concentrations, NO has been shown to reduce cell proliferation and to cause apoptosis (3,65).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants may therefore silence transcriptional activity (109,110), while pro-oxidants, such as arsenic trioxide, may reactivate the viral reservoir (112). By the same token, both NO donors and endogenously generated NO may stimulate HIV reactivation (113). Relatedly, Kahn et al (114) showed that anticancer conditioning agents (doxorubicin, etoposide, fludarabine phosphate, or vincristine) were able to induce HIV escape from latency and that this was associated with increased apoptosis rates (114).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
“…This suggests the possibility that cytokine/NOSassociated airway epithelial pH buffering could help prevent spread of HRV in the lower airway; HRV rarely causes true pneumonia in immunocompetent hosts. Of note, NOS activation itself, presumably independently of pH, can inhibit viral replication, both through S-nitrosylation-based inhibition of viral cysteine proteases (31,43) and through impaired hostdefense gene regulation (49). Furthermore, a fall in pH results in 1) augmented protein S-nitrosylation (43) and 2) conversion of nitrite to NO (25), both of which could augment the antiviral effect of NOS products.…”
Section: Discussionmentioning
confidence: 99%